1961
DOI: 10.1021/ja01485a025
|View full text |Cite
|
Sign up to set email alerts
|

Carbenes from Derivatives of Ethynylcarbinols. The Synthesis of Alkenylidenecyclopropanes1

Abstract: Aikenylidenecyclopropanes have been synthesized in moderate yields by reactions of derivatives of ethynylcarbinols with base in the presence of olefins.Evidence for the formation of diarylvinylidene carbenes as intermediates in the formation of tetraarylhexapentaenes is given.A faction scheme involving 7-elimination to give alkenylidene carbenes is proposed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
29
0

Year Published

1967
1967
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(29 citation statements)
references
References 2 publications
0
29
0
Order By: Relevance
“…In 1961, Hartzler investigated the ozonolysis of cyclopropenyl allenes and was possibly the first to propose the occurence of an alkenyl peroxide in solution . Reaction of 42 in ethanol generated α‐hydroxy‐ester 43 , in addition to acetone as the major product (Scheme ).…”
Section: Solution Chemistrymentioning
confidence: 99%
“…In 1961, Hartzler investigated the ozonolysis of cyclopropenyl allenes and was possibly the first to propose the occurence of an alkenyl peroxide in solution . Reaction of 42 in ethanol generated α‐hydroxy‐ester 43 , in addition to acetone as the major product (Scheme ).…”
Section: Solution Chemistrymentioning
confidence: 99%
“…[21] The synthesis of compound 37 was achieved by addition of propenylidene to 1,1-dimethylindene using the method of Hartzler [22] (Scheme 17). After separation of the exo and endo isomers, the respective enantiomers could be separated by HPLC, using a triacetylcellulose column and providing the isomers in optically pure form.…”
Section: Thermolysis Of 33mentioning
confidence: 99%
“…Ϫ MS (70 eV); m/z (%): 148(14) [M ϩ ], 133 (84), 115(15), 105 (100), 91 (56), 77(28), 65(22), 51(19), 41 (53). 139.3.…”
mentioning
confidence: 99%
“…(Dimethylvinylidene)carbene (1), which was generated easily by the elimination of hydrogen halides from propargyl halides 2 or haloallenes 3 has been used extensively in the stereospecific cyclopropanation of olefins to give the corresponding cyclopropanes (Scheme 1).1, 5 Hartzler has found that a more alkyl substituted olefin possesses greater relative reactivity toward the addition of carbene 1.…”
Section: Introductionmentioning
confidence: 99%